2023
DOI: 10.5194/essd-15-963-2023
|View full text |Cite
|
Sign up to set email alerts
|

National CO2budgets (2015–2020) inferred from atmospheric CO2observations in support of the global stocktake

Abstract: Abstract. Accurate accounting of emissions and removals of CO2 is critical for the planning and verification of emission reduction targets in support of the Paris Agreement. Here, we present a pilot dataset of country-specific net carbon exchange (NCE; fossil plus terrestrial ecosystem fluxes) and terrestrial carbon stock changes aimed at informing countries' carbon budgets. These estimates are based on “top-down” NCE outputs from the v10 Orbiting Carbon Observatory (OCO-2) modeling intercomparison project (MI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 185 publications
2
50
0
Order By: Relevance
“…Our model‐based analysis indicates that for the 2003–2015 study period the Arctic‐boreal region, as a whole, was a NEE sink (−850 Tg CO 2 ‐C year −1 , with an associated uncertainty of ±744–1138 Tg CO 2 ‐C year −1 ). This finding is closely aligned with atmospheric budgets from the OCO‐2 MIP LNLGIS experiment (Byrne, Baker, et al, 2022; Byrne, Liu, et al, 2022), which used satellite‐retrieved column‐averaged dry‐air atmospheric mole fractions (providing finer‐spatial tracking of CO 2 ), in addition to in situ CO 2 measurements. For bottom‐up models, our results were most closely within the range of two EC tower and remote‐sensing informed machine learning approaches—FluxCom RS + METEO (Jung et al, 2020) and Virkkala et al (2021).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our model‐based analysis indicates that for the 2003–2015 study period the Arctic‐boreal region, as a whole, was a NEE sink (−850 Tg CO 2 ‐C year −1 , with an associated uncertainty of ±744–1138 Tg CO 2 ‐C year −1 ). This finding is closely aligned with atmospheric budgets from the OCO‐2 MIP LNLGIS experiment (Byrne, Baker, et al, 2022; Byrne, Liu, et al, 2022), which used satellite‐retrieved column‐averaged dry‐air atmospheric mole fractions (providing finer‐spatial tracking of CO 2 ), in addition to in situ CO 2 measurements. For bottom‐up models, our results were most closely within the range of two EC tower and remote‐sensing informed machine learning approaches—FluxCom RS + METEO (Jung et al, 2020) and Virkkala et al (2021).…”
Section: Discussionsupporting
confidence: 80%
“…SMAP L4_C and CLM 5.0 indicated a small NEE source (8 and 21 Tg CO 2 ‐C year −1 ), relative to a much larger source (245 Tg CO 2 ‐C year −1 ) estimated by FluxCom RS. Whereas TCFM‐Arctic, the ACI ensemble (Liu et al, 2020), the OCO‐2 MIP experiments (Byrne, Baker, et al, 2022; Byrne, Liu, et al, 2022), FluxCom RS + METEO and Virkkala et al (2021) showed a small to moderate NEE sink (−16, −21, −49 to −32, −80, −97 Tg CO 2 ‐C year −1 , respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations